Manifesta young women, feminism, and the future - Baumgardner, Jennifer 1970-; Richards, Amy 1970- (New York Farrar, Straus and Giroux, 2010)
Studies the history, politics, and popular culture surrounding feminism and discusses how feminism has changed in the twenty-first century.
A day without feminism -- The dinner party -- What is feminism? -- Feminists want to know : is the media dead? -- Girl, you will be a woman soon -- Barbie vs. the menstrual kit -- Thou shalt not become thy mother -- Who's afraid of Katie Roiphe? -- What is activism? -- A day with feminism.
"Updated and with a new preface by the authors."--Cover.
Includes bibliographical references (pages 403-412) and index.
Keywords: Feminism -- United States; Young women -- United States -- Attitudes